The European funds and their economical effects in Romania - Liliana Marcela Durgheu; Rica Ivan (Agora International Journal of Economical Sciences (AIJES), 2016)
The absorption of the communitarian funds constitutes an objective on its own in the post-adherence strategy, taking into consideration the huge contribution that these funds will have in the recovery of the gap between our country and the other European Union member states. Using the European policy of cohesion, the access to these financial resources represents one of the main economical benefits.
Keywords: 330